THE INFLUENCE OF FINANCIAL LITERACY AND BUSINESS CAPITAL ON THE SUSTAINABILITY OF WOMEN-OWNED MSMEs IN LIMBOTO SUBDISTRICT, GORONTALO REGENCY - Mohamad Reyhan Permata; Muliyani Mahmud; Nurharyati Panigoro; Hendra Pratama Danial (PT. Jurnal Center Indonesia Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, including those managed by women. However, the sustainability of MSMEs still faces various challenges, particularly regarding low financial literacy and limited business capital. These conditions can affect the ability of female entrepreneurs to manage and develop their businesses sustainably. This study aims to determine the influence of financial literacy and business capital on the sustainability of women-owned MSMEs in Limboto Subdistrict, Gorontalo Regency. The method used in this study is a quantitative method with primary data obtained from questionnaires using a Likert scale. The sample collection process used the proportionate stratified random sampling technique. The strata in this study consisted of 14 villages in Limboto Subdistrict, Gorontalo Regency, with a total sample of 175 respondents. The data analysis technique employed Structural Equation Modeling (SEM), operated using the AMOS 24 program. The results of the study indicate that financial literacy does not have a significant effect on business sustainability, while business capital has a positive and significant effect on business sustainability. Furthermore, financial literacy and business capital simultaneously have a positive and significant effect on business sustainability, explained by an R-square value of 94.6%, while the remaining 5.4% is contributed by other variables outside the research model.